ESTUDO DE CONCRETO RECICLADO INCORPORANDO AGREGADO MIÚDO RECICLADO E SÍLICA ATIVA - Figueiredo, Marcela; Leite, Mônica (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this work is to evaluate the concrete behavior with recycled fine aggregate (RFA) in replacement of the natural fine aggregate (NFA), incorporating 3% of silica fume. Two water/cement ratios (0,48 and 0,61) were evaluated, and for each one were obtained a reference mixture and two other with 10 and 20% of RFA replacing the NFA. The workability of recycled mixtures was achieved adding superplasticizer. In the hardened state there was an improvement in compressive strength with the use of RFA and silica fume. Regarding the durability, all concretes studied were classified as normal concretes.